PRAWO RZYMSKIE W DAWNEJ ANGLII W ŚWIETLE POGLĄDÓW ARTURA DUCKA (WYBRANE ZAGADNIENIA) - Marzec, Łukasz (Zeszyty Prawnicze, 2017)
The Views of Arthur Duck on Roman Law in England Summary The aim of this paper is to discuss the views of sir Arthur Duck on the influence and power of Roman Law in England up to 17th century, which he analysed in his work De Usu et Authoritate Juris Civilis Romanorum in Dominiis Principum Christianorum first published in 1652. Chapter 8 of this book seems to be an important source for the contemporary research. Duck, a legal practitioner, a politician and a D. C. L. presented a unique view on the matter. A detailed study shows that the following areas and solutions of the English legal system bear signs of the Roman influence: courts (e. g. Court of Chancery, Court of Admiralty, Court of the Constable and Marshall), lectures at the Oxford University, Vacarius school of law, early English legal writings, legal theory and science. Duck was probably the first to notice and mark the striking similarity between Roman procedure of the ius honorarium and the English equity. He disagrees with the general opinion that the Roman Law exercised no authority in England.